مختار الدین احمد آرزوکے مکاتیب بنام سید معین الرحمٰن - Sabahat Moeen Saeed (Tabeer e Nau, 2025)
In Rakmah's article, linguist-researcher. Critic, editor, expert of Ghailbyat and educationist Dr.Mukhtar - ud - din Ahmad Arzoo (14th November 1924 _30 June 2010) with a brief introduction, 15 letters with footnotes are included. These letters are named after the educationist, researcher, editor and expert of Ghalibyat Dr. Syed Moeen ur Rehman (4th November 1942 _15th August (2005) These letters are in the family of Dr. Syed Moeen ur Rahman. It will be correct to say that Dr. Mukhtar -ud - din Ahmad Arzoo and Dr. Syed Moeen ur Rahman's long-standing relationship is almost 25 years old. Along with academic and literary topics. This article will help the readers to understand the entire literary situation of the era of literature. This article will help entire literary situation of the era of literature